The structure and stability of the low-index surfaces of D8m-Mo5Si3 by first-principles calculations. Issue 1 (January 2020) - Gu, S.; Sun, S.P.; Li, X.P.; Lei, W.N.; Rashad, M.; Yin, L.; Wang, Y.X.; Chen, L.Y.; Jiang, Y.
Abstract: Atomic relaxations, surface energies and electronic structures of the (100), (001) and (110) surfaces for D8m -Mo5 Si3 are investigated to analyze the surface stability by DFT (Density Functional Theory) based first-principles plane-wave pseudo-potential calculations. The atomic relaxation and surface energy results reflect minimum relaxations of the (ns-8Mo4Si)-terminated (001), (ns-4Si)-terminated (110) and (ns-2Si-2)-terminated (100) surfaces. Moreover, the (ns-8Mo4Si)-terminated (001) and (ns-4Si)-terminated (110) surfaces are most stable under Si-poor and Si-rich conditions, respectively. The density of states indicates that the surface electronic structures are mainly influenced by the atomic relaxations. The calculated charge densities show dependence of the surface relaxation mainly on dangling bonds. According to the calculated surface energies, the predicted crystal shapes show the octagonal prism and a structure which is close to cuboid in the μ S i s l a b - μ S i b u l k range from −1.077 eV to −0.546 eV and −0.546 eV–0 eV, respectively. These calculation results are compared with the previous reports.